Antioxidant agent Probucol beneficial influence on incidence and severity of coronary artery restenosis after transluminal balloon coronary angioplasty - A. I. Kaminny; V. Z. Lankin; V. I. Kaminnaya; E. I. Perepelitsa; Yu. A. Shuvalova; A. N. Samko; V. V. Kukharchuk (Кардиоваскулярная терапия и профилактика)
Aim. To study perspectives of reducing incidence and severity of coronary artery (CA) restenosis by adding a low dose of antioxidant agent Probucol (250 mg/d) to the treatment before and after transluminal balloon coronary angioplasty (TBCA). Material and methods. The study included 81 patients (mean age 55±6,5 years in Probukol group; 53±6 years in control group; total cholesterol (TCH) level – 6,2±0,66 mmol/l and 6,77±0,79 mmol/l, respectively) with chronic coronary heart disease (CHD), who underwent TBCA and coronaroangiography (CAG) 6 months later. The angiograms were assessed by quantitative computer analysis. Results. In atherosclerosis patients, antioxidant agent Probucol was highly effective not only in the lipid-lowering dose (1000 mg/d), but also in a four-fold reduced dose (250 mg/d). After six-month Probucol treatment (250 mg/d), restenosis incidence was just 19%, comparing to 28% in the control group. In Probucol group, minimal CA lumen diameter was significantly greater, and CA stenosis severity – significantly lower than in control group. Conclusion. The results obtained proved the possibility to reduce restenosis severity by Probucol treatment, even in low dose (250 mg/d), without affecting lipid profile.